Learning Engagement in Primary Education: Development and Validation of a Contextualized Scale for Indonesian Elementary School Students - Wicaksono, Meidias Abror; Purwanto, Edy; Raharjo, Tri Joko; Apsari, Diani Akmalia; Subali, Bambang; Widiarti, Nuni (Jurnal Kajian Bimbingan dan Konseling, 2025)
This study aims to develop and examine the validity and reliability of a contextual learning engagement scale for elementary school students. The scale was develop based on the learning motivation and behavior theory by Schunk, Pintrich, and Meece, and interest dimensions from Ainley. A quantitative approach using instrument development design was employed. Data analysis was conducted using confirmatory factor analysis (CFA) to evaluate the construct structure. A total of 330 students from grades 4, 5 and 6 were selected through cluster random sampling. The results revealed that the scale consists of four dimensions: learning enthusiasm, learning persistence, learning autonomy, and learning reflection. All dimensions met the requirements for construct, convergent, and discriminant validity, with Average Variance Extracted (AVE) values exceeding 0.50. Additionally, the reliability coefficients, including Cronbach’s Alpha and Composite Reliability, were both above 0.86. The model fit evaluation indicated that 9 out of 10 indices met the fit criteria. These findings demonstrate that learning engagement is a multidimensional construct that can be reliably measured in elementary education settings. The scale is expected to serve as a practical assessment tool for teachers, guidance and counseling, researchers, and policymakers in designing learning strategies that promote students active engagement.